Revealing glycoproteins in the secretome of MCF-7 human breast cancer cells - Tan, A.A.; Phang, W.M.; Gopinath, S.C.B.; Hashim, Onn Haji; Kiew, Lik Voon; Chen, Yeng (Hindawi Publishing Corporation, 2015)
Breast cancer is one of the major issues in the field of oncology, reported with a higher prevalence rate in women worldwide. In attempt to reveal the potential biomarkers for breast cancer, the findings of differentially glycosylated haptoglobin and osteonectin in previous study have drawn our attention towards glycoproteins of secretome from the MCF-7 cancer cell line. In the present study, further analyses were performed on the medium of MCF-7 cells by subjecting it to two-dimensional analyses followed by image analysis in contrast to the medium of human mammary epithelial cells (HMEpC) as a negative control. Carboxypeptidase A4 (CPA4), alpha-1-antitrypsin (AAT), haptoglobin (HP), and HSC70 were detected in the medium of MCF-7, while only CPA4 and osteonectin (ON) were detected in HMEpC medium. In addition, CPA4 was detected as upregulated in the MCF-7 medium. Further analysis by lectin showed that CPA4, AAT, HP, and HSC70 were secreted as N-glycan in the medium of MCF-7, with HP also showing differentially N-glycosylated isoforms. For the HMEpC, only CPA4 was detected as N-glycan. No O-glycan was detected in the medium of HMEpC but MCF-7 expressed O-glycosylated CPA4 and HSC70. All these revealed that glycoproteins could be used as glycan-based biomarkers for the prognosis of breast cancer.